2018
DOI: 10.1002/cncr.31689
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for metachronous bilateral renal cell carcinoma: A Surveillance, Epidemiology, and End Results analysis

Abstract: Background Patients treated for renal cell carcinoma (RCC) may be diagnosed with a metachronous, contralateral tumor. We evaluated the risks of contralateral tumor development using the Surveillance, Epidemiology, and End Results database. Methods Among RCC patients, we identified those with a metachronous, contralateral RCC diagnosed ≥1 year after primary diagnosis. We performed a competing risks analysis to evaluate associations between clinicopathologic factors and metachronous, bilateral RCC. Cumulative in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…However, when considering contralateral kidney tumors, it is evident that the elderly patients do not have an increased risk. Our univariate analysis found that the risk of patients over 60 years-of-age was lower for contralateral kidney SPM than that of patients under 44 years-of-age; this was consistent with previous literature [20,21]. Age itself is an independent risk factor for cancer [22], and because the risk of developing tumors increases with age.…”
Section: Survival and Risk Predictors Following The Diagnosis Of Primsupporting
confidence: 92%
“…However, when considering contralateral kidney tumors, it is evident that the elderly patients do not have an increased risk. Our univariate analysis found that the risk of patients over 60 years-of-age was lower for contralateral kidney SPM than that of patients under 44 years-of-age; this was consistent with previous literature [20,21]. Age itself is an independent risk factor for cancer [22], and because the risk of developing tumors increases with age.…”
Section: Survival and Risk Predictors Following The Diagnosis Of Primsupporting
confidence: 92%
“…Older age may lead to immunosenescence in these survivors ( 21 ), increasing the second cancer disease ( 22 , 23 ). Interestingly, like the results of previous studies in other tumors ( 24 , 25 ), black race increases the risk of SPMs in male CC survivors, especially for a second primary prostate carcinoma ( 3 ). We unexpectedly found higher risk to develop a SPM for married male CC patients, probably resulting from the impact of marital status on the occurrence of prostate carcinoma, and similar results showed that older, separated or divorced men existed a decreased risk for the development of prostate cancer ( 26 ), which is not easily explained.…”
Section: Discussionsupporting
confidence: 81%
“…A case of sporadic bilateral ccRCC was studied by single-cell transcriptome sequencing. Compared with many previous works on bilateral RCC (33)(34)(35) the present study firstly examined the tumour cellular biological characteristics of bilateral ccRCC at the single-cell level. Although large samples of DNA, bulk RNA and DNA methylation in ccRCC have been reported (29,30) these results only revealed the characteristics of RCC from an average level; specifying these attributes to cell types, especially tumour cells, is difficult.…”
Section: Discussionmentioning
confidence: 99%